Role of an Orthodontist in Managing Social Stigma Due to Malocclusion - Bhavna Singh; Govind Kumar Saxena (Current Practice in Medical Science Vol. 8, 2022)
Malocclusion, or irregularity of the teeth beyond what is seen as normal, is a dental condition that affects thousands of people worldwide yet is totally curable and treatable. Malocclusion is common, and its orthodontic correction is well-documented in the literature. Physical appearance is known to negatively affect an individual’s self-confidence. Facial appearance and teeth play a vital role in determining an individual’s self-worth. Poor facial aesthetics often leads to low self-esteem, specially during the initial growing years of a child. The primary goal of this article is to comprehend the psychosocial impact and social stigma associated with malocclusion, how it affects our society, and how orthodontists can assist their patients in overcoming this stigma.